2001
DOI: 10.1073/pnas.191512398
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VI is a processive motor with a large step size

Abstract: Myosin VI is a molecular motor involved in intracellular vesicle and organelle transport. To carry out its cellular functions myosin VI moves toward the pointed end of actin, backward in relation to all other characterized myosins. Myosin V, a motor that moves toward the barbed end of actin, is processive, undergoing multiple catalytic cycles and mechanical advances before it releases from actin. Here we show that myosin VI is also processive by using single molecule motility and optical trapping experiments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
371
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 363 publications
(401 citation statements)
references
References 30 publications
27
371
0
3
Order By: Relevance
“…A large stroke size is probably essential to the processive stepping mechanism of dimeric myosin VI, which moves along actin with Ϸ36-nm strides, matching the pseudorepeat of the actin helix (4,5). Unlike myosin V, myosin VI has not used multiple IQ repeats to achieve a large stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large stroke size is probably essential to the processive stepping mechanism of dimeric myosin VI, which moves along actin with Ϸ36-nm strides, matching the pseudorepeat of the actin helix (4,5). Unlike myosin V, myosin VI has not used multiple IQ repeats to achieve a large stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A new puzzle arose when the stepping behavior of dimeric myosin VI was characterized by using single molecule techniques (4,5). Myosin VI, like myosin V, walks processively along actin by using a long stride that approximately matches the Ϸ36-nm pseudorepeat of the actin filament.…”
Section: A Long Stride and A Long Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, myosin VI has an elastic region which can be elongated, and takes a diffusive search during a step to create a large displacement with a significant variability. 29,30 Studies have shown that myosin VI is involved in cell migration, spermatoge-FIGURE 2. Structures of kinesin and myosin V. Conventional kinesin and myosin V form a dimer and walk processively on their track.…”
Section: Molecular Motorsmentioning
confidence: 99%
“…They are also known to be involved in cell migration, cell invasiveness, plasminogen activity and drug and radiation resistance (Martens et al, 1999). Myosin VI is expressed in a variety of cell types and is thought to play a role in membrane trafficking and and endocytosis (Rock et al, 2001;Yoshimura et al, 2001). Tubulin beta 4 is downregulated in hepatoma cells than in normal liver cells (Yu et al, 2000).…”
Section: Genes Related To Cell Adhesion and Motilitymentioning
confidence: 99%